Validation of the Need for Social Interaction Scale between Customer and Service Provider - López-Bonilla, Jesús Manuel; López-Bonilla, Luis Miguel (Review of Business Management, 2014)
With the consolidation of the services sector in the global economy, we need to study further the relationship between customer and service provider. This paper analyzed the validity and reliability of the need for social interaction between customer and service provider. This scale has been made by Dabholkar (1996), from the ideas of Langeard et al. (1981). There are relatively few studies with this scale, therefore this construct should be taken into account in future research about service interaction. This study is based on a sample of 819 undergraduates. The results suggest that the Need of Social Interaction is a brief, simple and reliable scale.